Pengembangan Video Pembelajaran Biologi Pada Tumbuhan Paku (Pteridophyta) Untuk Siswa Kelas VII Di SMP Islam 2 Kota Ternate - Mega Safitri; Muhammad Hidayat (Peneliti.net, 2022)
In this industrial era 4.0, an educator can create an interesting, creative, innovative and fun learning process, by utilizing some of the current good media to achieve the goals of the learning process. Because the fulfillment of the learning criteria can make the world of learning effective. The results of observations related to problems in the biology learning process at Islamic Junior High School 2 Ternate City indicate that teachers consider problems in learning to be related to students including the average value of learning material for ferns below the average as a result of which it has an impact on the low learning outcomes of biology. In addition, the limitations of learning media are the second learning problem experienced by teachers. This study uses the Research and Development (R&D) method by following the Borg and Gall procedures. Research and Development (R&D) is a research method used to develop products used in education and learning. The purpose of this study is to produce a product in the form of audio-visual video media and test the effectiveness of the product. The use of learning media in the learning process can help concrete concepts or ideas and generate motivation and stimulation for learning activities and even bring psychological effects on students. For students, the media can be a bridge for critical thinking. Learning videos make the lesson more interesting. Because it is equipped with audio visuals, the material is not only conveyed through words. By using video in the learning approach, learning is expected to be more meaningful and foster interest in learning in students. Based on the development of learning videos that have been carried out by three experts, namely media experts, material experts, linguists and group trials, it can be concluded that the media that has been made the final result shows that the learning media is valid. that the presentation value is 3.694 (good).